Reproductive Rights Knowledge, Health Care Utilization, and Contraceptive Use in Pakistan: A Reproductive Rights Perspective - Saeed S; Pillai V; Gouher A (Dove Medical Press, 2021)
Sadia Saeed,1 Vijayan Pillai,2 Azka Gouher3 1Department of Sociology, Quaid-i-Azam University, Islamabad, Pakistan; 2School of Social Work, University of Texas at Arlington, Arlington, TX, 76015, USA; 3Truth Iinternational, Islamabad, PakistanCorrespondence: Vijayan PillaiSchool of Social Work, University of Texas at Arlington, 211 South Cooper Street, Arlington, TX, 76019, USATel +1 817 681 3784Email Pillai@uta.eduIntroduction: This study investigates the effects of utilization of health care and the level of reproductive rights knowledge on contraceptive use. Current family planning programs in developing countries utilize a two-pronged strategy involving improvement of level of reproductive rights and, right to access health care systems. The effectiveness of this strategy in developing countries such as Pakistan remains poorly investigated. This study aimed at examining the effect of reproductive rights knowledge on contraceptive use.Methods: The target population is educated, 18- to 45-year-old married Pakistani women. The sample is composed of 160 nonrandomly selected purposive group of women. We gathered data using a structured questionnaire and analyzed the data using several multivariate methods such as latent class analysis and multiple classification analysis.Results: Our results suggest that reproductive rights knowledge has no direct effect on contraceptive use. Furthermore, the level of utilization of the health care system plays a significant intervening role between reproductive rights knowledge and contraceptive use.Discussion: Our results call for improving access and availability of health care while strengthening the awareness and knowledge of reproductive rights among women to improve their capacity to utilize family planning methods. Public awareness and educational programs are indeed necessary to promote knowledge of reproductive rights among women in developing countries. As public health campaigns propagandize the crucial role reproductive rights play in improving women’s reproductive health, it is important to maintain a structurally harmonious relationship between health care systems and family planning programs promoting contraceptive use. This approach is more likely to result in significant returns for public awareness campaigns promoting reproductive rights in developing countries.Keywords: reproductive health, women’s rights, multiple classification analysis, Pakistan